2021
DOI: 10.1016/j.onehlt.2021.100221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climatic, demographic and disease control factors on the transmission dynamics of COVID-19 in large cities worldwide

Abstract: Approximately a year into the COVID-19 pandemic caused by the SARS-CoV-2 virus, many countries have seen additional “waves” of infections, especially in the temperate northern hemisphere. Other vulnerable regions, such as South Africa and several parts of South America have also seen cases rise, further impacting local economies and livelihoods. Despite substantial research efforts to date, it remains unresolved as to whether COVID-19 transmission has the same sensitivity to climate observed for other common r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…In other terms, climatic variables have much weaker explanatory power compared to non-climatic factors. Such findings are also consistent with previous studies available in the literature (e.g., [32,58]), supporting the hypothesis that socio-economic and epidemic response factors explained the greatest proportion of variance in the COVID-19 cases estimated. Our results also support the WHO's guidelines not to raise expectations that the COVID-19 outbreak will significantly slow because of changes to climate conditions alone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In other terms, climatic variables have much weaker explanatory power compared to non-climatic factors. Such findings are also consistent with previous studies available in the literature (e.g., [32,58]), supporting the hypothesis that socio-economic and epidemic response factors explained the greatest proportion of variance in the COVID-19 cases estimated. Our results also support the WHO's guidelines not to raise expectations that the COVID-19 outbreak will significantly slow because of changes to climate conditions alone.…”
Section: Discussionsupporting
confidence: 92%
“…Note that due to a lack of sufficient data for the considered countries, the non-climatic factors such as socio-economic, epidemic response, demographic, and geographic factors are not modeled. This approach is similar to that one used in [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why 2,491 valid correlation coefficients were obtained instead of 2,777 observations is that some of the original studies did not provide sufficient information on the specific modelling factors they used. For example, some studies did not mention the significance level (e.g., Ghosh et al 2020;Lin et al 2020;Daneshvar et al 2021); other studies either did not mention the number of observation days or time period (e.g., Wu et al 2020;Metelmann et al 2021;Pan et al 2021). Thus, these correlation coefficients were excluded from the meta-regression analysis.…”
Section: Accepted For Publication Inmentioning
confidence: 99%
“…Generally, in geographical terms, environment factors are categorized into natural environmental factors and human environmental factors ( Wu et al, 2021 ). Some worldwide studies have indicated that both natural and human environmental factors are crucial for COVID-19 transmission and the SARS-CoV-2 virus ( Fronteira et al, 2021 ; Metelmann et al, 2021 ; Rahimi et al, 2021 ; Srivastava, 2021 ). As an airborne transmission pandemic, SARS-CoV-2 and the severity of COVID-19 infection have been proven to be affected by climate conditions and air pollutants ( Domingo et al, 2020 ; Al Huraimel et al, 2020 ; Nottmeyer and Sera, 2021 ).…”
Section: Introductionmentioning
confidence: 99%